2017
DOI: 10.1007/s11277-017-4080-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Handover Decision Algorithm for Multimedia Streaming in VANET

Abstract: International audienceVehicular ad hoc networks represent one of the most important applications of wireless ad hoc networks. In highways, where different networks exist, frequent and sometimes unnecessary switches from one network to another may occur, which degrade network performance and affect applications, especially those that require high quality networks such as multimedia applications (Video conferencing, Video On-Demand, etc.). This work presents an analytical model and a Vertical Handover decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Compute Source node location and velocity (C 0 [mth Slot], V 0 [mth slot]); (5) Deploy relay node at C 0 (m + 1); (6) if Update message of relay fails then (7) Pick another Relay node from pool U i ; T update (8) Update T update � t; (9) endif (10) elseif i ϵ [1, n] then (11) Get update message from source node U 0 ; (12) Compute C i [m + 1]; (13) Synchronize Trajectory along Source node ( 14) endif (15) end for BS reply to Ui with reserve slot for U0; (7) end if (8) else if U0 also Compute BS > RSSI threshold (9) U0 send vertical handover request through Ui (10) BS allocate resource to Uo on behalf of Ui (11) Confirmation sent to relay node Ui and source node U0 (12) U0 initiate authentication (13) BS responds to authentication (14) U0 send confirmation message to relay node (15) end if ALGORITHM 2: Vertical handover using cooperative relaying.…”
Section: Relay Selection and Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Compute Source node location and velocity (C 0 [mth Slot], V 0 [mth slot]); (5) Deploy relay node at C 0 (m + 1); (6) if Update message of relay fails then (7) Pick another Relay node from pool U i ; T update (8) Update T update � t; (9) endif (10) elseif i ϵ [1, n] then (11) Get update message from source node U 0 ; (12) Compute C i [m + 1]; (13) Synchronize Trajectory along Source node ( 14) endif (15) end for BS reply to Ui with reserve slot for U0; (7) end if (8) else if U0 also Compute BS > RSSI threshold (9) U0 send vertical handover request through Ui (10) BS allocate resource to Uo on behalf of Ui (11) Confirmation sent to relay node Ui and source node U0 (12) U0 initiate authentication (13) BS responds to authentication (14) U0 send confirmation message to relay node (15) end if ALGORITHM 2: Vertical handover using cooperative relaying.…”
Section: Relay Selection and Deploymentmentioning
confidence: 99%
“…In the existing literature, significant attention has been given to the handover decision algorithms [12]. e work presented in [13] focused on the false handover initiation and ensured the true need for handover. In [14], the importance of finding the exact location of the base station for an effective handover process is emphasized to minimize failure and increase the success rate of the handover.…”
Section: Introductionmentioning
confidence: 99%
“…Ali Hassoun et al [27] proposed a VHDA algorithm by keeping the location of the vehicle, speed of the vehicle, and jitter as parameters. Simulated results have shown that VHDA algorithm outperforms the competitve approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2017, a highway-based handover decision method was proposed to solve the unnecessary handovers and to reduce the vertical handover frequency by considering the nodes' velocity, jitter, position and density. In addition, it was also essential to evaluate the packet loss, network throughput and end-to-end delay to present a complete network performance [8].…”
Section: Previous Work On Vertical Handover In Vanetmentioning
confidence: 99%